Transcultural adaptation and psychometric properties of Spanish version of Pregnancy Physical Activity Questionnaire: the PregnActive project - Miguel Ángel Oviedo-Caro; Javier Bueno-Antequera; Diego Munguía-Izquierdo (Elsevier, 2019)
Objective: To transculturally adapt the Spanish version of Pregnancy Physical Activity Questionnaire (PPAQ) analyzing its psychometric properties. Methods: The PPAQ was transculturally adapted into Spanish. Test-retest reliability was evaluated in a subsample of 109 pregnant women. The validity was evaluated in a sample of 208 pregnant women who answered the questionnaire and wore the multi-sensor monitor for 7 valid days. The reliability (intraclass correlation coefficient), concordance (concordance correlation coefficient), correlation (Pearson correlation coefficient), agreement (Bland-Altman plots) and relative activity levels (Jonckheere-Terpstra test) between both administrations and methods were examined. Results: Intraclass correlation coefficients between both administrations were good for all categories except transportation. A low but significant correlation was found for total activity (light and above) whereas no correlation was found for other intensities between both methods. Relative activity levels analysis showed a significant linear trend for increased total activity between both methods. Conclusions: Spanish version of PPAQ is a brief and easily interpretable questionnaire with good reliability and ability to rank individuals, and poor validity compared with multi-sensor monitor. The use of PPAQ provides information of pregnancy-specific activities in order to establish physical activity levels of pregnant women and adapt health promotion interventions. Resumen: Objetivo: Adaptar transculturalmente la versión española del Pregnancy Physical Activity Questionnaire (cuestionario de actividad física en el embarazo) analizando sus propiedades psicométricas. Método: El cuestionario de actividad física en el embarazo fue transculturalmente adaptado al español. La fiabilidad test-retest se evaluó en una submuestra de 109 embarazadas. La validez se evaluó en una muestra de 208 embarazadas que respondieron el cuestionario y llevaron colocado el monitor multisensor durante 7 días válidos. Se valoraron la fiabilidad (coeficiente de correlación intraclase), la concordancia (coeficiente de correlación de concordancia), la correlación (coeficiente de correlación de Pearson), el grado de acuerdo (gráfico Bland-Altman) y los niveles de actividad relativos (test Jonckheere-Terpstra) entre las dos administraciones y los dos métodos. Resultados: Los coeficientes de correlación intraclase entre las dos administraciones fueron buenos para todas las categorías, excepto el transporte. Una correlación baja, pero significativa, se encontró para la actividad total (suave y superior), mientras que no se encontró correlación para otras intensidades entre los dos métodos. El análisis de los niveles de actividad relativos mostró una tendencia lineal significativa para el incremento de actividad total entre ambos métodos. Conclusiones: La versión española del cuestionario de actividad física en el embarazo es un breve y fácilmente interpretable cuestionario, con buena fiabilidad y habilidad para ordenar personas, y baja validez en comparación con el monitor multisensor. El uso del cuestionario de actividad física en el embarazo aporta información sobre actividades específicas del embarazo con el objetivo de establecer los niveles de actividad física de las mujeres embarazadas y adaptar intervenciones para la mejora de la salud. Keywords: Exercise, Life style, Pregnancy, Surveys and questionnaires, Health, Palabras clave: Ejercicio, Estilo de vida, Embarazo, Encuestas y cuestionarios, Salud